Pengaruh Pemberian Minuman Mix Juice terhadap Kadar Glukosa Darah dan Kebugaran Ibu Bersalin - Riana Pascawati; Nurhalim Shahib; Farid Husin (Jurnal Kesehatan, 2019)
Mix Juice is a mixture of fruits, nuts, and honey so it contains a lot of glucose and fructose. Glucose in the body functions as the main energy source to maintain fitness. This mix of juice drink can be consumed by the mother and quickly produces energy so that it can be an alternative to meet the nutritional needs of the mother during labor. This research was to analyze the effect of mixed juice drink on blood glucose levels and maternity fitness. This study was a Quasi-Experiment design with Randomized Control Trial. This randomized controlled trial study has used a sample of 60 parturient at Bandung City Community Health Centers which divided into two groups: intervention and control.  Blood glucose level measured with a glucometer. Fitness was calculated from the pulse recovery using a pulse oximeter. Analysis using a T-Independent test. The results of the study showed significant differences in maternal blood glucose levels after drinking of mix juice, in the intervention group (34.7) and control group (16.4) with a value (p<0.05). There was fitness enhancement in the intervention group (0.32) contrast with a control group who had decreased (-2.21) with a value (p 0.05). The consumption of mix juice for parturient improve parturient’s glucose level and fitness.